2022
DOI: 10.1097/mph.0000000000002418
|View full text |Cite
|
Sign up to set email alerts
|

Response to Alpelisib in Clinically Distinct Pediatric Patients With PIK3CA-related Disorders

Abstract: PIK3CA-related disorders include vascular malformations, potential overgrowth of various tissues, limb abnormalities, disordered soft tissue, and/or fatty hyperplasia that often leads to significant morbidity. Alpelisib, a targeted inhibitor of p110α, an enzyme encoded by the PIK3CA gene, has demonstrated success in a cohort of patients with PIK3CA-driven overgrowth syndromes. We describe the clinical course of 2 pediatric patients treated with alpelisib under the Novartis Managed Access Program. Both patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…7,8 Consequently, hyperglycemia is a common adverse event of alpelisib in adults, 9,10 but less frequent in children possibly due to increased insulin sensitivity in this age group. 6,[10][11][12][13][14] Likewise, alpelisib could correct growth delay but could also stagnate linear growth. 6,13 In our patient, we measured IGF-1 after the initiation of alpelisib and, despite normal levels, her growth curve remained at À2 SD; therefore alpelisib induced growth delay could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Consequently, hyperglycemia is a common adverse event of alpelisib in adults, 9,10 but less frequent in children possibly due to increased insulin sensitivity in this age group. 6,[10][11][12][13][14] Likewise, alpelisib could correct growth delay but could also stagnate linear growth. 6,13 In our patient, we measured IGF-1 after the initiation of alpelisib and, despite normal levels, her growth curve remained at À2 SD; therefore alpelisib induced growth delay could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Alpelisib has better efficacy than sirolimus in reducing LM caused by PIK3CA variants 19 . In addition, alpelisib also had a preventive and reversing effect on adipose overgrowth located in other areas of the body 20,21 . The latest conclusions showed that significant volume reduction of facial soft tissues can be seen after the administration of alpelisib for 1 month, and continuous use can achieve the outcomes of volume reduction of fat and LM, sebaceous nevus hypopigmentation, improvement of oral, and speech function, the drug is ineffective for skeletal deformities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, alpelisib also had a preventive and reversing effect on adipose overgrowth located in other areas of the body. 20,21 The latest conclusions showed that significant volume reduction of facial soft tissues can be seen after the administration of alpelisib for 1 month, and continuous use can achieve the outcomes of volume reduction of fat and LM, sebaceous nevus hypopigmentation, improvement of oral, and speech function, the drug is ineffective for skeletal deformities. 22 Targeted drugs offer new possibilities for the treatment of FIL: reducing soft tissue volume and infiltration through oral drugs, and then adjusting soft tissue and bone deformities together with surgery.…”
Section: Casementioning
confidence: 99%
“…Currently, alpelisib-a selective PI3Kα inhibitor-is being investigated and used in an experimental setting for patients with a PIK3CA or TEK mutation [83,84]. Another example is trametinib, which is a MEK inhibitor, and promising results have been reported in patients with complex lymphatic anomalies associated with mutations in the RASpathway [85].…”
Section: Medical Therapymentioning
confidence: 99%